Basis of moral culture in islam (Journal of Philosophy Culture and Political Science, 2018)
This article deals the questions of foundation of culture – humanism and morality in Islam. In modern society are increased the influence of religion and culture. Identified human duties to the community. The main duty is to be highly spiritual. Religion pays great attention to education of person, respect for elders, protection and assistance to junior is the responsibility of the youth. Much attention is paid to charity in Islam, assistance to the needy. The peculiarity of humanity is living in society and the relationship between people. Each person must protect the environment, fight for peace, not to give place discord. Islam calls for peace and tranquility, to guard against incorrect interpretation of the canons of the Koran. Also given permission for the organization of religious communities in the educational and cultural institutions, which must obey the laws of the state. Religious education contributes to the formation of the individual morality.Key words: religion, Islam, spirituality, youth, charity, environment, peace, the Koran, law, government, education, morality.